Teachers' Ability to Construct Learning Through the Scramble Learning Model Approach in Schools - Sarumaha, Martiman Suaizisiwa; Laiya, Rebecca Evelyn (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
This study aims to see how far the influence of the scramble-type cooperative learning model on student learning outcomes. The type of research used in this research is a quasi-experimental design. The results of this study indicate that; the implementation of the economic learning process with the scramble-type cooperative learning model is quite effective in producing students' ability to understand each material. Based on these results it can be said that the experimental class achieved a score above the completeness criteria of learning outcomes compared to the learning scores of students in the control class. This cannot be separated from the teacher's ability to construct learning using the scramble learning model approach. So, through the learning construction of the scramble model, students can think critically and build their own capacity through various processes and learning models carried out in learning units.